Rare Diseases and Syndromes of the Spinal Cord - Eltorai, Ibrahim M. (Springer International Publishing : Imprint: Springer, 2016)
This book provides a comprehensive and up-to-date review of rare diseases and syndromes of the spinal cord, collected over the past forty years from all the world's literature. Each chapter in this volume is organized in the same easy-to-follow format, comprising definitions, incidence, etiology, clinical presentation, diagnosis, management, prognosis, and references. This book is aimed at medical students, residents, fellows, and junior attendings in spinal cord medicine, physical medicine, neurosurgery, orthopedics, oncology, emergency medicine, infectious disease, neurology, genetics, vascular surgery, and endocrinology, along with the numerous allied fields of physical therapy, nursing, occupational therapy, and biomedical researchers.